PERENCANAAN KEPALA SEKOLAH DALAM MENINGKATKAN MOTIVASI BELAJAR DI RAUDHATUL ATHFAL SUNAN KALIJOGO KARANG BESUKI - Mei Syaroh Endah Riwayanti; Muhammad Hanif; Eko Setiawan (Jurnal Dewantara, 2021)
The development of an educational institution cannot be separated from the intervention of a capable leader. The leadership in this case is the principal. The principal has a strategy used to develop the institution he leads. In this study, it will be explained how the strategies determined by the principal to increase learning motivation. The strategy consists of planning, implementing and evaluating the principal's program. The researcher uses a qualitative approach, as well as the type of case study research. Data collection techniques used are in-depth interviews, observation and documentation. The results showed that the strategy carried out by the principal had been planned, implemented according to the existing schedule, adjusted to the conditions around it, reported to the madrasa supervisor and solutions were sought if there were obstacles that arose during the implementation of the work program.